BS 5440-1. Chimneys, flue pipes and ventilation for gas appliances of rated input not exceeding 70 kW net (1st, 2nd and 3rd family gases). Part 1. Design, installation, commissioning and maintenance of chimneys. Specification (13th June 2023) - British Standards Institution,
No abstract available